Basal forebrain GABAergic neurons promote arousal and predatory hunting. (1st December 2020) - Cai, Ping; Chen, Li; Guo, Yu-Rou; Yao, Jing; Chen, Hui-Yun; Lu, Yi-Ping; Huang, Sheng-Nan; He, Peng; Zheng, Ze-Hong; Liu, Ji-Yuan; Chen, Jian; Hu, Li-Huan; et al.
Abstract: Predatory hunting is an important approach for animals to obtain valuable nutrition and energy, which critically depends on heightened arousal. Yet the neural substrates underlying predatory hunting remain largely undefined. Here, we report that basal forebrain (BF) GABAergic neurons play an important role in regulating predatory hunting. Our results showed that BF GABAergic neurons were activated during the prey (cricket)-hunting and food feeding in mice. Optogenetic activation of BF GABAergic neurons evoked immediate predatory-like actions to both artificial and natural preys, significantly reducing the attack latency while increasing the attack probability and the number of killed natural prey (crickets). Similar to the effect of activating the soma of BF GABAergic neurons, photoactivation of their terminals in the ventral tegmental area (VTA) also strongly promotes predatory hunting. Moreover, photoactivation of GABAergic BF - VTA pathway significantly increases the intake of various food in mice. By synchronous recording of electroencephalogram and electromyogram, we showed that photoactivation of GABAergic BF - VTA pathway induces instant arousal and maintains long-term wakefulness. In summary, our results clearly demonstrated that the GABAergic BF is a key neural substrate for predatory hunting, and promotes this behavior through GABAergic BF - VTA pathway. Highlights: The activity of BF GABAergic neurons is increased during the predation and feeding in mice. Photoactivation of BF GABAergic neurons elicits predatory attacks on preys, increasing attack probability and number of kills. Activating BF GABAergic terminals in the VTA strongly promotes predatory hunting. Activation of GABAergic BF-VTA pathway induces instant arousal and maintains long-term wakefulness.